Perfil tecnológico dos produtos exportados pelo Brasil para a China a partir dos determinantes do comércio internacional - Taliani, Giovani Cesar [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
This research assumes that the increase in technological levels of products exported by a given country is a relevant indicator of their development and, therefore, of national interest. The core of this work is to analyze the technological profile of the Brazil-China trade flow (export and import) from 2009 to 2020, through the database of the Secretary of Foreign Trade, Secex and Contrade. and to this end, the first chapter is dedicated to the presentation of this relationship. Thereafter, in the form of sub-chapters, the discussion on the problem of a possible Brazilian primarization, the issue of the hijacking of Brazilian domestic demand by China and, finally, the hypothesis that the Brazilian deindustrialization process takes place in a "natural" way, with no room to characterize it as negative. In the second chapter, it will be shown how Brazil can benefit from a more technologically sophisticated export agenda, i.e., with medium-high and high technology products and, especially, whether there would be a demand in the Brazil-China relationship for such products. Once the judgment on the benefits and advantages of increasing the proportion of technology-intensive products that are exported by Brazil, and specifically to China, is peaceful, this research will search in recent literature, proposals for the development and expansion of the Brazilian manufacturing industry in order to improve Brazil's export basket. The analysis will be based on the classification of technological intensity proposed by the OECD, and the enumeration of the products being made through the Common MERCOSUL Nomenclature (NCM).

A presente pesquisa parte do pressuposto de que o aumento dos níveis tecnológicos dos produtos exportados por determinado país é um relevante indicador de seu desenvolvimento e, portanto, de interesse nacional. O cerne deste trabalho é analisar o perfil tecnológico do fluxo de comércio (exportação e importação) Brasil-China no período de 2009 a 2020, através da base de dados da Secretária de Comercio Exterior, Secex e do CONTRADE, e para tanto, o primeiro capitulo é dedicado a apresentar esta relação. A partir disso, na forma de subcapítulos, será exibida a discussão sobre a problemática da possível primarização brasileira, o tema do vazamento da demanda doméstica brasileira para a China e por último, sobre a hipótese de que o processo de desindustrialização brasileiro se dá de forma “natural”, não havendo espaço para caracteriza-la como negativa. No segundo capitulo, será demonstrado como o Brasil pode se beneficiar de uma pauta exportadora mais sofisticada no aspecto tecnológico, isto é, com produtos de média-alta e alta tecnologia e principalmente, se haveria demanda na relação Brasil-China para tais produtos. Uma vez pacífico o juízo a respeito dos benefícios e proveitos ao se incrementar a proporção de produtos intensivos em tecnologia que são exportados pelo Brasil, e em específico para a China, esta pesquisa buscará na bibliografia recente, proposições para o desenvolvimento e ampliação da indústria de transformação brasileira afim de aprimorar a pauta exportadora do Brasil. A classificação de intensidade tecnológica será feita a partir da proposta pela OCDE, sendo a enumeração dos produtos feita através da Nomenclatura Comum do Mercosul (NCM).
Technological profile of products exported from Brazil to China based on the determinants of international trade.
Keywords: International Economics; International Trade; Export Trade; Import Trade; Economia Internacional; Comércio Internacional; Exportação; Importação